2021
DOI: 10.1177/14614448211020691
|View full text |Cite
|
Sign up to set email alerts
|

How behavioral homophily on social media influences the perception of tie-strengthening within young adults’ personal networks

Abstract: This study examines how social media and information-sharing behavior can influence young adults’ perceptions of changes in tie strength within their own personal networks. By focusing on the extended personal networks (27.56 relationships) of young adults, we show that social media leads them to feel closer to their “friends” whom they think of as exhibiting online behaviors similar to their own. This behavioral homophily mainly stems from frequent reactions between friends, when they like or comment upon eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
3
0
2
Order By: Relevance
“…While previous studies have demonstrated that social ties are more likely to be formed and maintained among homogeneous people, for example, in terms of place of residence and shared social media content [ 46 , 47 ], in this study, peers connecting via SNS showed higher heterophily regarding gender, age, educational attainment, working status, place of residence, hobbies/interests, and values for health than those connecting via other media, especially among respondents with lower educational attainment (data not shown). We assumed that such heterogeneity was effective in facilitating respondents’ access to useful health information.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have demonstrated that social ties are more likely to be formed and maintained among homogeneous people, for example, in terms of place of residence and shared social media content [ 46 , 47 ], in this study, peers connecting via SNS showed higher heterophily regarding gender, age, educational attainment, working status, place of residence, hobbies/interests, and values for health than those connecting via other media, especially among respondents with lower educational attainment (data not shown). We assumed that such heterogeneity was effective in facilitating respondents’ access to useful health information.…”
Section: Discussionmentioning
confidence: 99%
“…Partindo-se do princípio da homofilia [McPherson et al 2001, Figeac andFavre 2021], considerou-se que os usuários de cada cluster teriam predominantemente a mesma posic ¸ão (contrária ou a favorável) em relac ¸ão à CPI. Assim, foi realizada a modelagem de tópicos separadamente nos textos dos retweets compartilhados pelos usuários de cada agrupamento majoritário e em cada base coletada.…”
Section: Modelagem De Tópicosunclassified
“…A detecc ¸ão de posicionamento tem uma longa tradic ¸ão no domínio dos debates políticos e ideológicos online [Mohammad et al 2016] e a sua aplicabilidade prática permite avaliar a opinião pública, identificar grupos que se cruzam e divergem, e compreender questões de interesse para diferentes comunidades de usuários [Magdy et al 2016]. Estudos recentes sugerem que os usuários da web tendem a polarizar sua opinião [Conover et al 2011] e a formar comunidades a partir de afinidades políticas [Figeac and Favre 2021], seguindo o princípio da homofilia [McPherson et al 2001].…”
Section: Introduc ¸ãOunclassified
“…An individual that chooses to move in a direction opposed to others may find itself isolated for some period of time, and thus faced with making further decisions alone without access to the benefits of collective wisdom. Even without a spatial context, disagreements can fracture groups in contexts where homophily is a factor in determining social connections [16, 17]. Since being in a group allows an agent to access beneficial social information, this provides an incentive to follow the decisions made by others even if an individual has reason to believe that higher immediate rewards are available elsewhere, introducing a trade-off that is ignored by normative mathematical theories of social decision-making that focus on isolated choices.…”
Section: Introductionmentioning
confidence: 99%